Topographic location and connectivity to channel of earthquake- and rainfall-induced landslides in Loess Plateau area - Siyuan Ma; Xiaoyi Shao; Chong Xu; Xiaoli Chen; Renmao Yuan (Scientific Reports)
Abstract The position of landslides on a slope plays a crucial role in determining landslide susceptibility and the likelihood of landslide debris interacting with the fluvial system. Most studies primarily focus on shallow landslides in the bedrock weathering zone or large-scale bedrock landslides, but the relevant work about the location and connectivity to channels of loess landslides is limited despite their potential to provide insights into slope stability and material transport in loess regions. In this study, we explored differences in landslide location and connectivity to channels between 2013 Mw5.9 Minxian earthquake-induced (EQ) landslides and 2013 Tianshui rainfall-induced (RF) landslides in the Loess Plateau area, China. The result shows that more than 37% of EQ landslides occur in the vicinity of ridges and ~ 30% are concentrated near river channels. Landslide locations of the Minxian earthquake not only occur in ridge crest areas but also exhibit clustering near the channels. We attribute the former cluster to seismic shaking along the ridge crest, and the latter cluster to dynamic changes in pore pressure within saturated lower hillslopes due to nearly a month of rainfall prior to the Minxian earthquake. Compared to EQ landslides, RF landslides are more evenly distributed across slopes. However, due to heavy rainfall and river erosion, landslides are more concentrated in the middle and lower slope areas, especially near the river channels. Moreover, the connectivity of landslides to channels indicates that RF landslides exhibit stronger connectivity with river channels compared to EQ landslides, which may be related to the concentration of EQ landslides near ridge areas. Furthermore, due to the smaller scale of EQ landslides compared to RF landslides, larger landslides are more likely to be located closer to river channels. This may contribute to the lower observed connectivity index between EQ landslides and river channels.